Partidos armados: La lógica oficial y las voces disidentes (Argentina, 1976-1977) - Maria Matilde Ollier (Nuevo mundo - Mundos Nuevos, 2008)
The article shows the emergence within the Ejército Revolucionario del Pueblo and the Montoneros, of dissident voices that contested some actions and statements of their leaders. Organized or not, such voices were a sort of resistance against the orders expressed by guerrilla superiors, above all after the Ezeiza massacre. This article argues that divergences between armed factions became visible not only because the illegal repression carried out under the Peronist government (most notably by the paramilitary squad called Triple A) nor due to other practices of State Terrorism, but because of the disobedient tendencies that appeared among followers in response to political positions adopted by their leaders and the imposition of military discipline.